Ce(iv)-centered charge-neutral perovskite layers topochemically derived from anionic [CeTa2O7]− layers. Issue 45 (26th October 2021) - Hasegawa, Takuya; Yamasaki, Naoki; Asakura, Yusuke; Ueda, Tadaharu; Yin, Shu
Abstract : This study proposed a new layer modification technique, "layer charge control", for layered perovskites, and the structures of the obtained charge neutral [CeTa2 O7 ] perovskite sheet were characterized theoretically and experimentally. Abstract : Layered perovskites have been extensively investigated in many research fields, such as electronics, catalysis, optics, energy, and magnetics, because of the fascinating chemical properties that are generated by the specific structural features of perovskite frameworks. Furthermore, the interlayers of these structures can be chemically modified through ion exchange to form nanosheets. To further expand the modification of layered perovskites, we have demonstrated an advance in the new structural concept of layered perovskite "charge-neutral perovskite layers" by manipulating the perovskite layer itself. A charge-neutral perovskite layer in [Ce IV Ta2 O7 ] was synthesized through a soft chemical oxidative reaction based on anionic [Ce III Ta2 O7 ] − layers. The Ce oxidation state for the charge-neutral [Ce IV Ta2 O7 ] layers was found to be tetravalent by X-ray absorption fine structure (XAFS) analysis. The atomic arrangements were determined through scattering transmission electron microscopy and extended XAFS (EXAFS) analysis. The framework structure was simulated through density functional theory (DFT) calculations, the results of which were in good agreement with those of the EXAFS spectra quantitative analysis. The anionic [Ce III Ta2 O7 ] − layers exhibited optical absorption in the near infrared (NIR) region at approximately 1000 nm, whereas the level of NIR absorption decreased in the [Ce IV Ta2 O7 ] charge-neutral layer due to the disappearance of the Ce 4f electrons. In addition, the chemical reactivity of the charge-neutral [Ce IV Ta2 O7 ] layers was investigated by chemical reduction with ascorbic acid, resulting in the reduction of the [Ce IV Ta2 O7 ] layers to form anionic [Ce III Ta2 O7 ] − layers. Furthermore, the anionic [Ce III Ta2 O7 ] − layers exhibited redox activity which the Ce in the perovskite unit can be electrochemically oxidized and reduced. The synthesis of the "charge-neutral" perovskite layer indicated that diverse features were generated by systematically tuning the electronic structure through the redox control of Ce; such diverse features have not been found in conventional layered perovskites. This study could demonstrate the potential for developing innovative, unique functional materials with perovskite structures.